SYMBOLISM USED IN SIKKA KROWE’S WEDDING CEREMONY OF MAUMERE, EAST NUSA TENGGARA - Anselmus Teng; Rusfandi Rusfandi; Trisno Tunggal Rahayu Wilujeng (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2015)
A symbol is an object that represents an idea, image, visual, belief, action, or material. They are used to convey ideas and beliefs. This means symbol can give the direction for those in choosing certain tools that are used to get their mission. Here, symbol is the expression of a thing that cannot be signed with the right sign. Symbols are alive as long as they have the meanings. Every place in Indonesia has its own culture. One of them is Sikka Krowe’s culture of Maumere, East Nusa Tenggara. Sikka Krowe is the special call for one of the ethnic groups in Maumere. It is in Sikka regency area. Sikka itself is the name that refers to a small traditional village known as Sikka Natar (Kampung Sikka). Krowe refers to people in countryside from Nele (west of Sikka regency) to Tanah Ai (east of Sikka regency). Therefore, the researcher is interested in studying this culture in debt by formulating three research questions: (1) How is the procedure of Sikka Krowe’s weding ceremony of Maumere. (2) what kinds of symbols used in Sikka Krowe’s wedding ceremony of Maumere? (3) What are the meaning of those symbols?. The researcher found the kinds of symbols that are revealed in Sikka Krowe’s wedding ceremony like in daily life such as wua ta’a, tua/moke/arak, manu ama and manu muhun, wair hu’er, bala, mu’u, kalar gelang, jarang, tudi, wawi ireng,reng-reng, utan, kila, pagat uma, bolo plagar and lensu widin tilun. . This is the symbol of the simplicity of life. The process of wedding ceremony requires some conditions regulated and set by the norms and traditions.